Restorative Justice in Criminal Acts of Losing Human Life from an Economic Perspective - Marwa, Soffa; Mandala, Subianta (Asian Journal of Social and Humanities, 2025)
This study analyzes in depth the implementation of restorative justice (RJ) in the crime of killing a person in Indonesia from an economic perspective. Using qualitative methods with normative legal and conceptual approaches, and secondary data analysis, this study examines the potential benefits and challenges of implementing RJ in murder cases. The results of the analysis show that RJ has the potential to offer social and economic benefits—such as better victim recovery, potential reduction in long-term criminal justice system costs, and reduced recidivism—compared to retributive approaches. However, its implementation in Indonesia faces significant obstacles, including regulatory fragmentation, institutional resistance, public perception, and limited resources and local empirical data. While immediate cost savings may be limited for serious cases, the potential long-term socio-economic benefits of recovery and social cohesion could be substantial. Effective implementation requires legal harmonization, resource investment, paradigm shift, and the development of clear guidelines. The findings of this study highlight the economic and social potential of implementing restorative justice (RJ) in Indonesia’s criminal justice system, particularly in cases of homicide. From an economic perspective, RJ could reduce the long-term costs associated with the criminal justice process, such as incarceration and administrative expenses, by focusing on rehabilitation and reintegration of offenders.